Non-invasive neuromodulation in reducing the risk of falls and fear of falling in community-dwelling older adults: systematic review - Bueno, Guilherme Augusto Santos; do Bomfim, Arthur Dutra; Campos, Lorrane Freitas; Martins, Anabela Correia; Elmescany, Raquel Brito; Stival, Marina Morato; Funghetto, Silvana Schwerz; de Menezes, Ruth Losada (Frontiers in Aging Neuroscience, 2024)
Introduction Neuromodulation is a non-invasive technique that allows for the modulation of cortical excitability and can produce changes in neuronal plasticity. Its application has recently been associated with the improvement of the motor pattern in older adults individuals with sequelae from neurological conditions. Objective To highlight the effects of non-invasive neuromodulation on the risk of falls and fear of falling in community-dwelling older adults. Methods Systematic review conducted in accordance with the items of the Cochrane Handbook for Systematic Reviews of Interventions. Searches were carried out in electronic databases: CENTRAL, Clinical Trials, LILACS, PEDro, PubMed, Web of Science, between 13/06/2020 and 20/09/2023, including all indexed texts without language and publication date restrictions, randomized controlled clinical trials, which presented as their main outcome non-invasive neuromodulation for reducing the fear of falling and risk of falls in the older adults, regardless of gender. Results An extensive search identified 9 eligible studies for qualitative synthesis from 8,168 potential articles. Rigorous filtering through automated tools, title/abstract screening, and full-text evaluation ensured a focused and relevant selection for further analysis. Most studies (80%) used transcranial direct current electrical stimulation as an intervention, over the motor cortex or cerebellum area, with anodal current and monopolar electrode placement. The intensity ranged from 1.2 mA to 2 mA, with a duration of 20 min (80%). The profile of the research participants was predominantly individuals over 65 years old (80%), with a high risk of falls (60%) and a minority reporting a fear of falling (40%). The outcomes were favorable for the use of neuromodulation for the risk of falls in the older adults, through improvements in static and dynamic balance. Conclusion The results may have limited applicability to direct outcomes related to the risk of falls, in addition to evidence regarding the difference or lack thereof in applicability between genders, fallers and non-fallers, as well as older adults individuals with low and high fear of falling. Systematic review registration The protocol for this review was registered in the International Prospective Register of Systematic Reviews (PROSPERO) to obtain the identification of ongoing research (ID: 222429).